2020
DOI: 10.3390/ijerph17041244
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation of Hospitalization Rates for Asthma in Korea: Association with Ambient Carbon Monoxide and Health Care Supply

Abstract: This study was performed to investigate the relationship between the hospitalization rate for asthma and the ambient carbon monoxide (CO) by examining regional variation of the hospitalization rates for asthma in Korea and its factors. The hospital inpatient claims for asthma were acquired from the National Health Insurance database in 2015. A multivariate linear regression was performed with the hospitalization rate for asthma as a dependent variable. The annual ambient concentration of CO showed a negative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…In the analysis of CO, SO 2 and O 3 , protective effects were observed, which lowered the morbidity risk for 18%, 19%, 18% per IQR increase respectively, different from some previous findings ( Szyszkowicz et al, 2018 ; Tao et al, 2014 ; Zhu et al, 2020 ). Yet prior studies have given some evidence suggesting a protective role of low-concentration exposure of gaseous pollutions on respiratory diseases as well as asthma ( Cai et al, 2015 ; Kim et al, 2020 ; Tian et al, 2013 ). In particular, the 24-h concentrations of CO, SO 2 and maximum 8-h average O 3 were below the China national air pollution standard of 4mg/m 3 , 50μg/m 3 and 100μg/m 3 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the analysis of CO, SO 2 and O 3 , protective effects were observed, which lowered the morbidity risk for 18%, 19%, 18% per IQR increase respectively, different from some previous findings ( Szyszkowicz et al, 2018 ; Tao et al, 2014 ; Zhu et al, 2020 ). Yet prior studies have given some evidence suggesting a protective role of low-concentration exposure of gaseous pollutions on respiratory diseases as well as asthma ( Cai et al, 2015 ; Kim et al, 2020 ; Tian et al, 2013 ). In particular, the 24-h concentrations of CO, SO 2 and maximum 8-h average O 3 were below the China national air pollution standard of 4mg/m 3 , 50μg/m 3 and 100μg/m 3 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The plausible explanation for the linear positive relationships observed in this study is the relatively higher ambient CO concentration during the study period in Ganzhou. By contrast, the ambient CO concentrations in those studies that reported the protective effects of CO were 0.58 mg/m 3 in Korea in 2015 ( 28 ) and 0.72 mg/m 3 in Hong Kong from 2001 to 2007 ( 38 ), while the average ambient CO concentration was 1.2 mg/m 3 with a range from 0.6 to 2.9 mg/m 3 in Ganzhou. Furthermore, different study designs (including different city, hospital, and population structures), social institutions, and cultures may also account for the inconsistencies.…”
Section: Discussionmentioning
confidence: 79%
“…The positive association of ambient CO exposure with asthma has been found in the general population, children, or several specific months of the year ( 25 27 ) in several studies. On the other hand, several studies indicated that there was no association or even a negative association between ambient CO exposure and asthma ( 28 , 29 ). Synthesizing the design and methods of the aforementioned studies, these differences may largely be due to the differences in the study population, and children with asthma seemed to be more vulnerable to ambient CO exposure because of their immature lung development.…”
Section: Discussionmentioning
confidence: 99%
“…Covariates were designated based on diagnosis codes of ICD-10. The covariates considered in this study were diabetes, dyslipidemia, [14] myocardial infarction (MI), stroke, [18] heart failure, [16] liver disease, cancer, chronic obstructive pulmonary disease (COPD), [19] asthma, [20] end-stage renal disease (ESRD) with dialysis, [15] and immunocompromised status including autoimmune diseases and HIV infections. [21] Definitions of each comorbidity are presented in Table S1 in the Supplement.…”
Section: Definition Of Covariatesmentioning
confidence: 99%
“…[14][15][16][18][19][20][21] Also, considering the rigorous control of national health insurance system of South Korea in the diagnosis of COVID-19,…”
mentioning
confidence: 99%